Constructions of Leadership Identities via Narratives of African Women School Leaders - Moorosi, Pontso (Frontiers in Education, 2020)
This paper explores African women school leaders’ constructions of their leadership identity. Using self-perception theory, wherein changes in self-perceived leadership skills and dispositions are related to changes in perceived leader identity, constructions of African women’s leadership identity are mapped over a life-long career. Leader identity is in this sense inextricably linked to gender and an attempt is therefore made to understand these leader identities as gendered. The paper is an analysis of three women’s interviews selected from a bigger study of 89 school leaders from four countries in sub-Saharan Africa. The three narratives of women leader identity construction drawn from three of the four case study countries. A narrative approach to data analysis reflecting women school leaders’ experiences of leader identity construction involved reading of transcripts and coding them with themes characterising processes of becoming a leader and being identified as one. Findings suggest that processes of becoming a leader are influenced by women leaders’ experiences of early socialisation that installed in them, ways of doing leadership as well as values and attributes that shape their approach to leadership. These women grow up with a strong perception of who they are, which instils a sense of agency that facilitates leaderful actions. These actions get affirmed through their different stages of growth and career development strengthening their leader identity. The paper concludes that understanding women leaders’ experiences of leader identity is an important ingredient of leadership development.